Digital ID and the Data Protection Challenge : Practitioner's Note - Clark, Julia; Daly, Conrad (World Bank, Washington, DC, 2019)
Inclusive and trusted identification (ID) systems are crucial tools for achieving sustainabledevelopment, including the World Bank Group’s twin goals of ending extreme poverty and ofboosting shared prosperity and greater equity in the developing world.3 Indeed, the essential rolethat identification plays in development is explicitly recognized in Sustainable Development Goal(SDG) Target 16.9, to “provide legal identity for all, including birth registration” by 2030.Traditionally, proof of identity has been provided through physical documents, such as birthcertificates, passports, or ID cards. As the world becomes increasingly digitized, the nextgeneration of ID systems use new technologies to provide digital proof of legal identityfor in-person and remote transactions. These digital ID systems can help achieve multipledevelopment goals, but also create challenges for digital privacy and data protection. This notedescribes these risks and then presents concrete steps to mitigate them while harnessing the fullpotential of digital ID for development.